Anthropometric characteristics and changes with HIV and ART in a randomly selected population in the Drakenstein region Western Cape Province - Beukes, Dillan Charles (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.